2019
DOI: 10.1089/neu.2018.5734
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Correlates of Mild Traumatic Brain Injuries in Women Subjected to Intimate-Partner Violence: A Preliminary Study

Abstract: A large proportion (range of 44-75%) of women who experience intimate-partner violence (IPV) have been shown to sustain repetitive mild traumatic brain injuries (mTBIs) from their abusers. Further, despite requests for research on TBI-related health outcomes, there are currently only a handful of studies addressing this issue and only one prior imaging study that has investigated the neural correlates of IPV-related TBIs. In response, we examined specific regions of white matter microstructure in 20 women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 45 publications
4
72
0
Order By: Relevance
“…To the authors knowledge there is no research on this topic in retired female athletes; however, there is limited evidence on the effect of repetitive, mostly mild, traumatic brain injuries in women subjected to intimate-partner violence. [65][66][67] Similar to our results, the authors found moderate correlations across studies between measures of learning/memory and brain injury scores (based on frequency and recency). Additionally, learning/memory performance and brain injury scores were associated with abnormalities on neuroimaging.…”
Section: Neurocognitive Performance and Cognitive Symptomssupporting
confidence: 89%
“…To the authors knowledge there is no research on this topic in retired female athletes; however, there is limited evidence on the effect of repetitive, mostly mild, traumatic brain injuries in women subjected to intimate-partner violence. [65][66][67] Similar to our results, the authors found moderate correlations across studies between measures of learning/memory and brain injury scores (based on frequency and recency). Additionally, learning/memory performance and brain injury scores were associated with abnormalities on neuroimaging.…”
Section: Neurocognitive Performance and Cognitive Symptomssupporting
confidence: 89%
“…1,13,15,16 Moreover, a substantial percentage of women experience repetitive TBIs as a result of intimate partner violence. [17][18][19][20] Current scientific guidelines strongly advise considering sex and gender in analyzing and reporting outcomes and treatment effects. [21][22][23] Some studies have shown that women have less access and lower rates of direct transfers to trauma centers 6,24 and fewer admissions to intensive care 25 after traumatic injuries.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we, along with others, have chosen to include IPV-related strangulation injuries with TBI (Campbell et al, 2018;Kwako et al, 2011;St. Ivany & Schminkey, 2016;Valera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%